The Exposed Proteomes of Brachyspira hyodysenteriae and B. pilosicoli - Casas, Vanessa (Front Microbiol, 2016)
Brachyspira hyodysenteriae and Brachyspira pilosicoli are well-known intestinal pathogens in pigs. B. hyodysenteriae is the causative agent of swine dysentery, a disease with an important impact on pig production while B. pilosicoli is responsible of a milder diarrheal disease in these animals, porcine intestinal spirochetosis. Recent sequencing projects have provided information for the genome of these species facilitating the search of vaccine candidates using reverse vaccinology approaches. However, practically no experimental evidence exists of the actual gene products being expressed and of those proteins exposed on the cell surface or released to the cell media. Using a cell-shaving strategy and a shotgun proteomic approach we carried out a large-scale characterization of the exposed proteins on the bacterial surface in these species as well as of peptides and proteins in the extracellular medium. The study included three strains of B. hyodysenteriae and two strains of B. pilosicoli and involved 148 LC-MS/MS runs on a high resolution Orbitrap instrument. Overall, we provided evidence for more than 29,000 different peptides pointing to 1625 and 1338 different proteins in B. hyodysenteriae and B. pilosicoli, respectively. Many of the most abundant proteins detected corresponded to described virulence factors and vaccine candidates. The level of expression of these proteins, however, was different among species and strains, stressing the value of determining actual gene product levels as a complement of genomic-based approaches for vaccine design.